Clinical and radiological analysis of the effects of three different lumbar transpedicular dynamic stabilization system on disc degeneration and regeneration - Karadag, Mehmet Kursat; Akgun, Mehmet Yigit; Basak, Ahmet Tulgar; Ates, Ozkan; Tepebasili, Mehmet Ali; Gunerbuyuk, Caner; Oktenoglu, Tunc; Sasani, Mehdi; Ozer, Ali Fahir (Frontiers in Surgery, 2023)
Objective: To assess the clinical outcomes of three transpedicular dynamic systems in degenerative disc disease, evaluating their impact on both clinical and radiological aspects of the operated and adjacent segments.Methods: A total of 111 patients who underwent posterior transpedicular short segment dynamic system procedures for degenerative disc disease were included. Patients were categorized into three groups: Group 1 (Dynesys system, n=38), Group 2 (Safinaz screw + Peek rod, n=37), and Group 3 (Safinaz screw + Titanium rod, n=36). Disc regeneration in the operated segment and disc degeneration in the operated, upper, and lower adjacent segments were assessed using the Pfirrmann Classification.Results: Postoperatively, a statistically significant difference was observed in VAS and ODI scores (p<0.001). However, there was no statistically significant difference in disc degeneration/regeneration and degeneration scores of the upper and lower adjacent segments between preoperative and postoperative groups (p=0. 763, p=0.518, p=0.201).Notably, a positive effect on disc regeneration at the operated level (32.4%) was observed. No significant differences were found between groups regarding operation rates, screw loosening, and screw breakage after adjacent segment disease (p>0.05).In patients without advanced degeneration, all three dynamic systems demonstrated the ability to prevent degeneration in the adjacent and operated segments while promoting regeneration in the operated segment. Beyond inhibiting abnormal movement in painful segments, maintaining physiological motion and providing axial distraction in the operated segment emerged as key mechanisms supporting regeneration.